2007
DOI: 10.1196/annals.1403.009
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐Derived Neurotrophic Factor in Neuronal Survival and Behavior‐Related Plasticity

Abstract: Neurotrophins are critical to the development and maintenance of the mammalian central nervous system. Among them is brain-derived neurotrophic factor (BDNF), whose synthesis and release is targeted by activation of glutamate receptors. Perturbation of this process probably underlies neurodegenerative and psychiatric disorders. A naturally occurring variation in humans, in the form of a common single-nucleotide polymorphism in the pro region of the polypeptide at codon 66 (Val66-->Met), affects processing of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
215
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(221 citation statements)
references
References 88 publications
3
215
0
1
Order By: Relevance
“…Since BDNF is released from neurons and promotes neuronal survival, 43 and we observe a 50% BDNF reduction in these mice, our results suggest a non-autonomous effect. However, this does not exclude the possibility that Ca v 1.2 may also play a role in neuronal cell death by regulating calcium signaling in a cell-autonomous manner.…”
supporting
confidence: 54%
“…Since BDNF is released from neurons and promotes neuronal survival, 43 and we observe a 50% BDNF reduction in these mice, our results suggest a non-autonomous effect. However, this does not exclude the possibility that Ca v 1.2 may also play a role in neuronal cell death by regulating calcium signaling in a cell-autonomous manner.…”
supporting
confidence: 54%
“…Lower BDNF levels in the hippocampus of aged APP/ PS1 mice Brain-derived neurotrophic factor (BDNF) is a central regulator of hippocampal neuron survival and synaptic plasticity (Lipsky and Marini 2007). Levels of BDNF have been reported to be decreased in the preclinical Five mice per group for pathological analyses and three mice per group in three independent Western blotting analysis experiments.…”
Section: Resultsmentioning
confidence: 99%
“…BDNF is important in neuronal growth and survival and synaptic processes of memory (Lipsky and Marini 2007). Evidence has suggested that dysfunction of BDNF is a possible contributor to the pathology and symptoms of AD (Tapia-Arancibia et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF is an immediate early gene that responds rapidly after membrane depolarization, and is involved in the maintenance and support of neurons (Barde, 1994;Marini et al, 2008). It is essential in neuronal survival and behavior-related plasticity (Lipsky and Marini, 2007). BDNF induces anti-apoptotic mechanisms after stroke, and reduces infarct size and secondary neuronal cell death (Schabitz et al, 2000;Zhang and Pardridge, 2001).…”
Section: Discussionmentioning
confidence: 99%